7+3/y=y-6

Simple and best practice solution for 7+3/y=y-6 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 7+3/y=y-6 equation:



7+3/y=y-6
We move all terms to the left:
7+3/y-(y-6)=0
Domain of the equation: y!=0
y∈R
We get rid of parentheses
3/y-y+6+7=0
We multiply all the terms by the denominator
-y*y+6*y+7*y+3=0
We add all the numbers together, and all the variables
13y-y*y+3=0
Wy multiply elements
-1y^2+13y+3=0
a = -1; b = 13; c = +3;
Δ = b2-4ac
Δ = 132-4·(-1)·3
Δ = 181
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$y_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$y_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

$y_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(13)-\sqrt{181}}{2*-1}=\frac{-13-\sqrt{181}}{-2} $
$y_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(13)+\sqrt{181}}{2*-1}=\frac{-13+\sqrt{181}}{-2} $

See similar equations:

| m^2-70=-9m | | 5m+4m-9m+m+3m=8 | | 9x-4(-3)=72 | | 20t+5t-t-17t=7 | | 10u-9u=16 | | 6s-44=8(2+1/44s) | | x-84=8(2x+3)-3 | | -x2=4x+4 | | -3(x+2)+15=17-4x | | 9b=-123 | | 3(x+5)-3=32-2x | | 22-x=175+.35x | | 12b-10b+b-2b=15 | | (6x-9)+12=33 | | 35x-(1060+3.50x)=0 | | 4b+2b-5b+4b-4b=16 | | 180=x+2x-23 | | 3b-2b+2b-2b=20 | | 6g+g=6 | | 3(x+2)2^+26=0 | | 45=33-7(-4-3w) | | H(3)=-4x+7 | | 16q−8q=8 | | 10v-8v=12 | | 6(x+18−2x−3/16)=3(3/4x−14)−3/8(3x−2) | | 12-f+f=9 | | 6((x+18)−(2x−3/16))=3(3/4x−1/4)−3/8(3x−2) | | k/8.3+58.4=23.5 | | 11=x/2- | | 2√x+6−5=4 | | 3(7z=23)=99 | | 3x-15  =   3 • (x-5)   |

Equations solver categories